ANALISIS KELAYAKAN USAHA PENGOLAHAN KOPI PADA KOPERASI SERBA USAHA ASOSIASI PETANI KOPI MANGGARAI (KSU ASNIKOM) DI KOTA RUTENG, KABUPATEN MANGGARAI - Yuliana Maria Nabut; Maximilian M. J. Kapa; Sondang P. Pudjiastuti; Joni M. M. Aji (Buletin Ilmiah Impas, 2021)
Coffee is one of the plantation commodities that have a fairly high economic value. Now many people are trying their luck by building a coffee processing business to add to the selling value of coffee. The Manggarai Coffee Farmers Association (KSU ASNIKOM) is a coffee processing business entity established on July 14, 2010 chaired by Mr. Lodo Vadirdman. This research aims to find out the feasibility of coffee processing business at KSU ASNIKOM and the obstacles faced by KSU ASNIKOM. The research method used is the purposive sampling method. Data is analyzed with descriptive analysis methods and financial feasibility analysis methods. Descriptive analysis methods consist of aspects of market and marketing and organizational management and financial proper analysis methods are viewed from NPV, NET B/C, GROSS B/C, PP, IRR, PR The results of descriptive analyst methods show from the market and marketing aspects of the coffee sales process from KSU ASNIKOM conducted directly by KSU to Buyyer. Coffee sales through auctions, exports, also participate in coffee exhibition activities. In terms of organizational management aspects KSU ASNIKOM has had a plan from the beginning of its establishment about processing and marketing and has its own logo for KSU ASNIKOM. The results of the financial feasibility analysis showed the results of npv calculation of 340,407,191 > 0 with the criteria if npv > 0 then the business is worth continuing, the IRR value of 123% > discount rate (12%) is worth running, gross value B / C of 1.09 > 1, with gross value criteria B / C > 1 then the business is worth continuing, Nett Value B / C of 3.45 > 1, with the criteria of Nett value B / C > 1 then the business is said to be worthy to continue, Profitability Ratio value of 1.27 > 1, with the criteria of PR value > 1 business is profitable, and pp or period of return on investment that has been issued is for 3 years. The obstacles faced by KSU ASNIKOM are inadequate infrastructure facilities such as damaged roads and also the influence of bad weather makes coffee drying more time consuming.